Microwave-Assisted Synthesis of 4-Substituted 2-Methylthiopyrimidines - Thomann, Andreas; Börger, Carsten; Empting, Martin; Hartmann, Rolf W. (Synlett, 2014)
Typically, SNAr reactions at 4-chloro-2-methylthiopyrimidine are carried out employing DMF and sodium hydride under inert gas as well as prolonged reaction times. Herein, we describe a mild and rapid microwave-assisted synthesis to achieve 4-substituted 2-methylthiopyrimidnes from the corresponding chlorine precursor. Moderate to excellent yields were obtained in a green chemistry fashion requiring only few minutes of reaction time.
Keywords: green chemistry; pyrimidine; combinatorial chemistry; medicinal chemistry; nucleophilic aromatic substitution